Exploratory writing in student learning. Issue 1 (2nd January 2016) - Lee, Juyoung; Son, Jihyeong; Settle, Quisto
Abstract : Exploratory writing learning activities were developed to prepare for a final group presentation project in a course about social, psychological, and cultural aspects of dress in the fall of 2014, at a university in the southern United States. The purposes of this study were (1) to develop learning activities to incorporate exploratory writing on social, psychological, and cultural aspects of clothing class and (2) to analyse student learning based on the newly developed learning activities. Over a two-week span for the exploratory writing assignments, each individual student completed two short reading reflection assignments and two assignments that incorporated a short writing and a visual image. Groups of three or four students prepared 8-minute final group presentations. Utilising constant comparative analysis of students' reflective essays regarding exploratory writing activities for their final group presentation project, this research analysed the student learning process when exploratory writings were incorporated into their curriculum. The results showed the exploratory writing process helped students by increasing their learning through integrating affective and cognitive dimensions of their thinking to a subject matter.